PERICARDIUM DISEASES - A. A. Dyomin; V. P. Drobysheva (Российский кардиологический журнал)
The lecture summarizes published and our own data on etiology, diagnostics, management, prevention and prediction of pericarditis (PC), that is currently the most common type of pericardium diseases (PD) and quite common cause of chest pain. Causes of PD differ and usually are related to infections (viral and bacterial), neoplasms (primary and secondary), autoimmune disorders (connective tissue diseases and vasculitides), drugs and the syndrome of pericardial damage. Idiopathic/viral PC is the most common type of PD and shows recurrence in one third of patients. the diagnosis is based upon clinical and instrumental criteria (ECG, EchoCG, cardiac MR I, pericardium biopsy). In acute PC the most common treatments are NSAIDs, antiviral drugs and, additionally, colchicine (first line treatment). New treatment for recurrent PC is intravenous immunoglobulins or anakinra (second line treatment). In our own last series of patients the evolution of PD causes has been marked: tendency to increase of specific types of PC (tuberculosis, autoimmune) and appearance of novel iatrogenic types after cardiovascular interventions. Therapy with non-steroidal antinflammatory drugs and colchicine do decrease the rate of recurrents.